2011
DOI: 10.1002/cyto.a.21126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shear rate and suspending medium viscosity on elongation of red cells tank‐treading in shear flow

Abstract: Elongation measurements of red cells subjected to simple shear flow are usually performed using a single suspending medium (viscosity g 0 ) and varying the mean shear rate ð _ cÞ. Such data are often plotted versus the shear stress ðs ¼ g 0 _ cÞ suggesting that the elongation scales with s. In this work, normal blood samples were tested in a rheoscope varying both g 0 and _ c. The ranges of _ c were chosen to restrict the elongation of the red cells to low values where the behavior is dominated by their intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…It is not convenient to apply information from such simulations for interpretation of experimental observations of the suspending viscosity effect, since both the capillary number G and the viscosity ratio l vary with the suspending viscosity h o . Also, as noticed by Fischer and Korzeniewski (2011), only few numerical studies considered viscosity ratios in the range in rheoscope experiments, and the results from these limit simulations are not helpful for understanding the experimental observations.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…It is not convenient to apply information from such simulations for interpretation of experimental observations of the suspending viscosity effect, since both the capillary number G and the viscosity ratio l vary with the suspending viscosity h o . Also, as noticed by Fischer and Korzeniewski (2011), only few numerical studies considered viscosity ratios in the range in rheoscope experiments, and the results from these limit simulations are not helpful for understanding the experimental observations.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, even within the same suspending medium, Fischer (2007) noticed that the f , _ g curves exhibit a slightly convex fashion, indicating the increase of f with _ g slows down at high shear rates. Furthermore, recently Fischer and Korzeniewski (2011) performed thoughtful examination on the cell deformation data of TT RBCs, and they found that the suspending viscosity h o plays a slightly more important role than the shear rate _ g in determining the cell deformation, especially for low viscosities h o , 70 cP. In spite of these careful experimental investigations, the underlying mechanisms are still not well understood (Fischer 2007;Fischer and Korzeniewski 2011).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fischer & Korzeniewski (2011) studied the elongation of TT red cells varyingγ and η 0 . They found a threshold in η 0 above which the elongation was independent of cellular viscosities.…”
Section: Factors Determining τ Tmentioning
confidence: 99%